If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 2y = 3y + -6 Reorder the terms: -4 + 2y = -6 + 3y Solving -4 + 2y = -6 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -4 + 2y + -3y = -6 + 3y + -3y Combine like terms: 2y + -3y = -1y -4 + -1y = -6 + 3y + -3y Combine like terms: 3y + -3y = 0 -4 + -1y = -6 + 0 -4 + -1y = -6 Add '4' to each side of the equation. -4 + 4 + -1y = -6 + 4 Combine like terms: -4 + 4 = 0 0 + -1y = -6 + 4 -1y = -6 + 4 Combine like terms: -6 + 4 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2
| 22-10n+n^2=-2 | | -7m+13+8m-5= | | 7=3z+2 | | 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 | | .5x+.45(30)=49.5 | | -8m+15+9m=-2 | | Y=-4(4)-3 | | x-9+5x-3=5x | | 11x=10x+17 | | Y=-4(-2)-3 | | x-14.6=20 | | 5(k+2)=3(-4) | | -8m+15+9m-2= | | Y=-10(5)-3 | | n+221=333 | | 5m-13=33 | | 9x^4=3x^2-25 | | 5(5x)+12= | | 5(5x+12)= | | 4n+24=2n+42 | | 3p+5=2p+14 | | 2(13.5)+-1.5y+3y=27 | | 2*2*n*n=54 | | 12x=3x+12 | | 23xn=22135 | | 2(13.5+-1.5y)+3y=27 | | 5(y-3)+2(y+4)=42 | | 18x+6=3x+18 |